Controls of the conditions associated with the contract in Bahraini civil law and Islamic jurisprudence: comparative analytical study - AlMekhlafi, Abdullah Mohammed Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
This study deals with the controls of the conditions associated with the contract in Bahraini civil law and Islamic jurisprudence. The knowledge of conditions carries great importance in the financial transactions that take place between individuals in society, and in particular the contracts that are concluded between the contracting parties and the terms that contain these contracts and which are relied upon in The protection and guarantee of contracting funds, as the various contracts and actions through which individuals practice different transactions include many conditions, and on these conditions the validity and invalidity of contracts depend, and given the impact of the conditions on contracts, civil laws have interfered and legal controls have been set for the conditions that are set in the different contracts to protect it from nullity. This research aims mainly to define the legal and controls for the conditions associated with contracts in Bahraini civil law and Islamic jurisprudence, and to show the impact of conditions on the validity of contracts.This study has reached a number of results, the most important of which is that the principle in the conditions is permissibility and not prohibition, and it has restricted freedom in terms of contracts associated with contracts by placing exceptions on the original in order to achieve the public interest and the private interest, and adopting this principle is a desire of the Bahraini legislator not to restrict and limit the contracting parties. The permissibility of the conditions associated with contracts in specific conditions, and the study also showed that adherence to the legal controls related to the conditions protect contracts and actions from nullity, and the contracting parties avoid disputes and material losses that may befall them as a result of contract nullity in the event of Non-compliance with legal and legitimate Controls.
Keywords: Bahraini Civil Law; Conditions Attached to Contracts; Public Order; Islamic Jurisprudence